2021
DOI: 10.3389/fendo.2021.793431
|View full text |Cite
|
Sign up to set email alerts
|

Improving Voice Outcomes After Thyroid Surgery – Review of Safety Parameters for Using Energy-Based Devices Near the Recurrent Laryngeal Nerve

Abstract: Technological advances in thyroid surgery have rapidly increased in recent decades. Specifically, recently developed energy-based devices (EBDs) enable simultaneous dissection and sealing tissue. EBDs have many advantages in thyroid surgery, such as reduced blood loss, lower rate of post-operative hypocalcemia, and shorter operation time. However, the rate of recurrent laryngeal nerve (RLN) injury during EBD use has shown statistically inconsistent. EBDs generate high temperature that can cause iatrogenic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
(116 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, the “liquid–gas flow” generated by EBDs can also be a risk factor for RLN thermal injury ( 9 , 14 ). RLN thermal injury is severe and can lead to paralysis of the VC ( 15 , 16 ). Notably, it would be quite effective to isolate the RLN with lateral thermal spread and liquid–gas flow.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the “liquid–gas flow” generated by EBDs can also be a risk factor for RLN thermal injury ( 9 , 14 ). RLN thermal injury is severe and can lead to paralysis of the VC ( 15 , 16 ). Notably, it would be quite effective to isolate the RLN with lateral thermal spread and liquid–gas flow.…”
Section: Discussionmentioning
confidence: 99%
“…With the modernization of thyroid surgery, advances have included the use of energy-based devices (EBD) as an extension from the “clamp-and-tie” technique that Theodore Kocher fathered in the 19th century. Today, hemostasis can be achieved in multiple ways: clamp-and-tie, electrocautery (monopoloar or bipolar), with hemostatic clips, and more advanced EBD that use thermal, ferromagnetic, or ultrasonic energy to ligate, seal and dissect tissue ( 36 ). Even though more advanced techniques with EBD have demonstrated reduced pain, wound drainage, decreased rates of neck hematoma and even hypocalcaemia ( 37 40 ), the results for EBD are inconsistent in terms of rates of RLN injury compared with conventional approaches ( 41 , 42 ).…”
Section: Practice Recommendations To Minimize Dysphonia Post Thyroid ...mentioning
confidence: 99%
“…Several studies have demonstrated that traction and thermal injury are the first and second most common causes of iatrogenic RLN injury during thyroidectomy ( 39 , 43 , 44 ). As one would expect, the use of EBDs can generate high temperatures that can spread to critical structures such as the RLN causing indirect thermal spread or direct thermal injury ( 36 ). Thus, various guidelines are published to ensure that surgeons maintain a safe distance between the activated EBD tip and the surrounding soft tissue ( 36 ).…”
Section: Practice Recommendations To Minimize Dysphonia Post Thyroid ...mentioning
confidence: 99%
See 2 more Smart Citations